Hα emission and H ii regions at the locations of recent supernovae in nearby galaxies - Mayker Chen, Ness; Leroy, Adam K.; Sarbadhicary, Sumit K.; Lopez, Laura A.; Thompson, Todd A.; Barnes, Ashley T.; Emsellem, Eric; Groves, Brent; Chandar, Rupali; Chevance, Mélanie; Chown, Ryan; Dale, Daniel A.; et al. (The astronomical journal)
We present a statistical analysis of the local, ≈50-100 pc scale, Hα emission at the locations of recent (≤125 yr) supernovae (SNe) in nearby star-forming galaxies. Our sample consists of 32 SNe in 10 galaxies that are targets of the PHANGS-MUSE survey. We find that 41% (13/32) of these SNe occur coincident with a previously identified H ii region. For comparison, H ii regions cover 32% of the area within ±1 kpc of any recent SN. Contrasting this local covering fraction with the fraction of SNe coincident with H ii regions, we find a statistical excess of 7.6% ± 8.7% of all SNe to be associated with H ii regions. This increases to an excess of 19.2% ± 10.4% when considering only core-collapse SNe (CCSNe). These estimates appear to be in good agreement with qualitative results from new, higher-resolution Hubble Space Telescope Hα imaging, which also suggests many CCSNe detonate near but not in H ii regions. Our results appear consistent with the expectation that only a modest fraction of stars explode during the first ≲5 Myr of the life of a stellar population when Hα emission is expected to be bright. Of the H ii region associated SNe, 85% (11/13) also have associated detected CO (2-1) emission, indicating the presence of molecular gas. The SNe associated with H ii regions have typical extinctions of A V ∼ 1 mag, consistent with a significant amount of pre-clearing of gas from the region before the SNe explode.
Veröffentlicht: 18. Juni 2024
Gesehen am 29.11.2024